Ni(ii) complexes bearing pyrrolide-imine ligands with pendant N-, O- and S-donor groups: synthesis, structural characterization and use in ethylene oligomerization. Issue 111 (26th October 2015) - Pinheiro, A. C.; Virgili, A. H.; Roisnel, T.; Kirillov, E.; Carpentier, J.-F.; Casagrande, O. L.
Abstract : Nickel complexes bearing pyrrolide-imine ligands with pendant N-, O- and S-donor groups have been synthesized and their catalytic behavior in ethylene oligomerization has been investigated. Abstract : A series of new Ni(ii ) complexes of general formula LNiCl [Ni1, L = 2-(C4 H3 N-2′-CHN)C2 H4 NHPh;Ni2, L = 5- tert -butyl-2-(C4 H2 N-2′-CHN)C2 H4 NHPh;Ni3, L = 2-(C4 H3 N-2′-CHN)C2 H4 OPh;Ni4, L = 2-(C4 H3 N-2′-CHN)C6 H4 -2′-OPh;Ni5, L = 2-(C4 H3 N-2′-CHN)C6 H4 -2′-SPh;Ni6, L = 2-(C4 H3 N-2′-CHN)CH2 C6 H4 -2′-OMe] were prepared and fully characterized. All nickel precatalysts, activated with methylaluminoxane (MAO), exhibited moderate to good activities for ethylene oligomerization [TOF = 6.1–71.3 × 10 3 mol (C2 H4 ) (mol (Ni) −1 h −1 )] and producing high selectivities for 1-butene (68.3–94.0 wt%). The catalytic performance was substantially affected by the ligand environment regarding the pendant oxygen- and sulfur-donor groups, and the substituents on the pyrrolide group. Activation of nickel precatalystNi3 with ethylaluminum sesquichloride (Et3 Al2 Cl3, EASC) instead of MAO produced a significantly more productive catalyst system thanNi2 /MAO (TOF = 153 700 vs. 43 500 mol (C2 H4 ) (mol (Ni) −1 h −1 )); however, the 1-butene selectivity was drastically reduced, attaining only 53 wt% with a concomitant production of larger amounts of internal butenes (38 wt%). Under optimized conditions ([Ni] = 10 μmol, 30 °C, oligomerization time = 20 min, 20 bar ethylene, [Al]/[Ni] = 250), precatalystNi3 led to a TOF = 55 900 mol (C2 H4 ) (mol (Ni) −1 h −1 ) and 82.8 wt% selectivity for 1-butene.